2010
DOI: 10.1111/j.1095-8312.2010.01391.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of placentas and superfetation in the fish genus Poecilia (Cyprinodontiformes: Poeciliidae: subgenera Micropoecilia and Acanthophacelus)

Abstract: Complex adaptations are often found in nature, although our ability to discern how and why such traits evolved is limited because their origin occurred in the distant past and the details of their evolution have been lost through extinction (e.g. all placental mammals inherited their placentas from a single common ancestor that lived over 100 Mya). In poeciliid fishes, placentas have evolved independently multiple times and portions of the path to the evolution of complexity can be found in living species. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 59 publications
1
51
0
1
Order By: Relevance
“…However, sampling errors in classification have led to erroneous mapping of the trait onto phylogenies. For example, Pires et al (2010) recently found superfoetation in the lineage composed of Poecilia bifurca, P. branneri and P. parae, and this represents an additional independent origin of superfoetation that was previously unknown. In addition, more information is needed to clarify the spatial and temporal variation in this reproductive trait.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, sampling errors in classification have led to erroneous mapping of the trait onto phylogenies. For example, Pires et al (2010) recently found superfoetation in the lineage composed of Poecilia bifurca, P. branneri and P. parae, and this represents an additional independent origin of superfoetation that was previously unknown. In addition, more information is needed to clarify the spatial and temporal variation in this reproductive trait.…”
Section: Introductionmentioning
confidence: 93%
“…For instance, in their comprehensive summary of life histories within the family Poeciliidae, Reznick and Miles (1989) classified species as either superfoetating or non-superfoetating. Yet, ignoring intraspecific variation did lead to incorrect classifications; these authors put down Poecilia parae as nonsuperfoetating, but a subsequent study showed that females sometimes bear simultaneous broods (Pires et al 2010), a finding that revealed an additional independent evolutionary origin of superfoetation (Meredith et al 2011). Even repeated sampling, if limited, can lead to an underestimate of the number of species that undergo superfoetation.…”
Section: Variability In Superfoetation and Comparative Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Poeciliids are characterized by a suite of derived characters including the position of the pectoral fins high on side of the body, an anterior placement of the pelvic fins ventral to the pectoral fins, the presence of pleural ribs on the first several haemal arches, a bony cap on the ventral hypohyal lying over the anterior facet of the anterior ceratohyal, and supraorbital laterosensory pores with neuromasts embedded in fleshy grooves (Ghedotti, 2000). Despite the widespread use of poeciliid fishes in ecological and evolutionary studies (e.g., Rauchenberger, 1990;Meyer et al, 1994;Borrowsky et al, 1995;Marcus & McCune, 1999;Spencer et al, 1999;Spencer et al, 2000;Morris et al, 2001;Kallman et al, 2004;Gutierrez-Rodriguez et al, 2007a, 2007bReznick et al, 2007;Leberg & Firmin, 2008;Purcell et al, 2008;Martin et al, 2009;Pollux et al, 2009;Meredith et al, 2010;Pires et al, 2010;Albert & Johnson, 2011), the phylogenetic interrelationships among poeciliid species remain incompletely resolved.The family Poeciliidae comprises three subfamilies that are restricted to fresh and brackish continental waters: Poeciliinae, Procatopodinae, and Aplocheilichthyinae (Ghedotti, 2000;Lucinda, 2003;Hrbek et al, 2007). The Poeciliinae includes at least 228 species distributed across much of the tropical and subtropical portions of the Americas, from the La Plata estuary of northern Argentina to southeastern United States, with species richness reaching a zenith in Middle America and the West Indies (Rosen & Bailey, 1963;Lucinda, 2003;Hrbek et al, 2007;.…”
mentioning
confidence: 99%